The metric system /A Critical Study 0f its Principles and Practice - Danloux- Dumesnils M.; Garrett Anne; Rowlinson J. S. (London. : The Athlone Press, 1969)
Explains the principles and uses of the metric system.
Keywords: Metric system -- Juvenile literature; Metric system